Aplikasi Pelayanan Informasi Kendaraan Bermotor berbasis SMS Gateway (Studi Kasus : Samsat Kuningan) - Erlan Darmawan; Lingga Adiputra (NUANSA INFORMATIKA, 2013)
Vehicle data information must be known by every owner of a vehicle. However, sometimes people do not know a whole of a vehicle information regarding the vehicle data information. Even to find out the vehicle information, people should visit the SAMSAT office. Therefore to achieve excellent service, fast, and meet the public demand for improving services, it is necessary to use information technology in it, such as utilization-based SMS Gateway system. People can easily find out their vehicles information only by SMS (Short Message Service). The object of this paper is SAMSAT Office.The aim of vehicle services based on SMS Gateway is to facilitate the public to find out the vehicle information accurately without visiting the SAMSAT office of Kuningan. This paper uses Waterfall (waterfall cycle) method. In collecting the data, this paper uses the observation and interviews. By using observation and interviews, the writer would be known the flaws in the service of vehicle information.The conclusion reached in this paper is that the application of vehicle information service is very beneficial to the society because these applications can be easily used by any people to know the data of their vehicles.Keywords: SMS, SAMSAT, Waterfall